Estudo sobre a satisfação dos moradores e principais patologias decorrentes de ampliações em residências construídas com recursos do Programa Minha Casa Minha Vida na cidade de Campo Mourão, PR - Bijora, Helito (2013)
This work aims to assess the overall satisfaction of residents with the contemplated mortgage with funds from the housing program Minha Casa Minha Vida, consisted of interviewing more than 80 families in Campo Mourão. For this research, was developed a standard questionnaire with simple and objective questions about the quality of the houses and weaknesses. The results were outlined in charts to better define the critical points. Besides the survey, was identified the main pathologies caused by focusing on expansions, which are often performed without the accompaniment of a civil engineer technician for professional negligence and the lack of knowledge of the resident. Among the pathologies found, there is the appearance of cracks and leaks, checked in virtually every home visits, and secondary problems caused by such as mold and mildew. The paper also discussed the project area, comparing the houses built in housing programs decades ago with what is currently built in the city. Finally, after considering the views of the residents interviewed were proposed suggestions for improvements to the design model which is often practiced in popular building home, such as garage, larger rooms and possibility of expansion envisaged in the project.